Ectopic pregnancy: a diagnostic dilemma - Kumar, Saha Pradip; Pratiksha, Gupta; Poonam, Goel; Alka, Sehgal; Anju, Huria; Kataria, Shailja; Tandon, Rimpy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To study the etiology, varied clinical presentations and misdiagnosis in ectopic pregnancy. Methods: A retrospective analysis of all operated ectopic pregnancies over a 7 year period at Government Medical College & hospital, Chandigarh was done. Details of clinical findings and misdiagnosis were noted. Surgically confirmed cases were included in this study. Expectant management and Medical management cases were excluded in this study. Results: Two hundred eighty two cases of ectopic gestation were analyzed. Identifiable risk factor present in 221 cases (78.3%). Pain was the commonest presenting symptom and 78 cases (27%) were misdiagnosed before the correct diagnosis was made by our department. Conclusions: Ectopic pregnancy can have varied presentations and misdiagnosis can be seen in Surgical, Medical and Gynaecology Departments. A young female with amenorrhea, pain abdomen with or without vaginal bleeding in early pregnancy diagnosis of ectopic pregnancy must be kept in mind. Early diagnosis would help early intervention and thus reduce the morbidity.